CHANGES IN THE COMPONENTS OF THE NATURAL ENVIRONMENT WITH THE LONG-TERM DEVELOPMENT IN THE OPENCAST MINES (THE CASE OF KMA) - O. M. Zhitinskaya; L. A. Yarg (Известия высших учебных заведений: Геология и разведка, 2018)
The influence of the processes of functioning of the local natural-technical systems (NTS) «Stoilenskoe» and «Lebedinskoe» of the KMA deposit on the environment has been studied with the information obtained during the period of last 7—12 years (2004—2015 y.y.). Results of the analyses of time series and obtained trends in the geological components alteration (in particular, a) level of groundwater, b) chemical composition of groundwater, c) engineering and geological processes) have been given. The ways of regime observations optimization concerning their placement and frequency in time have been offered. The proposed way of the assessment of the current state of NTS allows reducing the observations number, without reducing quality of information. The spatial structure and the time mode of monitoring have to be corrected according to the obtained information. The data received from Lebedinskoye and Stoylinskoye fields can be used for design and development of the similar geological fields.